BUILD SETTLEMENTS IN THE TIDAL FLOOD AREA: LEARNING FROM FISHERMEN COMMUNITIES' COPING STRATEGIES FOR CLIMATE CHANGE - Jamilla Kautsary; Cynthia Ratih Susilo (International Conference on Coastal and Delta Areas, 2015)
Global warming and climate change cause some problems such as floods, droughts, storms, landslides and fires. Special problem in coastal areas is tidal flooding due to rising sea levels. This condition affects to the fisherman communities in the North of Central Java in building settlements and meets the needs of basic infrastructure such as water, waste water and garbage. This study aims to reveal more about how the fishing communities on the north coast to resolve the issue. Locus studies are in three settlements of fishermen in Semarang, Kendal and Tegal. The method used in this study is deductive qualitative rationalistic, with descriptive empiric analysis. From the results of a series of in-depth interviews, observation and empirical reduction, obtained several findings. First in building settlements: community will raise the floor elevation of buildings, roads and social facilities periodically; people use household garbage to raise the elevation of the land up to a certain height, and on the top of that area will covered with the soil; community use special foundation for their building construction with reinforcement material of bamboo. In the fulfillment of the basic infrastructure, people use dig wells, deep wells and buy water from water vendors circumference; community will throw garbage on the land pocket to be built or water body; and communities dispose of domestic waste both liquid and solid to the water body.Keywords: Settlements, Tidal Flood, Coping Strategy and Climat Change.